Pemanfaatan Bahan Organik Sebagai Bahan Baku Pupuk Kompos Program KKN-PMD Unram 2024 Di Desa Jero Gunung, Kabupaten Lombok Timur - Almiatullah, Almiatullah; Fitriani, Irma; Haq, Mahsa Dliyaul; putri , Ayu Rolita; Anugerahuriyahdini, Anugerahuriyahdini; Hasanah, Hardiatun; Rasyid, Mugni Al; Arrasyid, M. Rusli; Rozi, Fahrur; Putri, Ayu Rolita (Jurnal Wicara, 2025)
One of the problems in the Jero Gunung village community, Sakra Barat District, East Lombok Regency is the lack of public awareness to live healthily, especially related to littering. This waste problem has become the biggest problem in Jero Gunung village which is difficult to eliminate. Most of this waste comes from households. In addition to the waste problem, there is also a lot of livestock waste that can be used as compost. And seen from the agricultural side, Jero Gunung village also has quite large plantation potential such as coffee, chili, tomatoes and so on. In rice fields, rice is usually planted in the rainy season while in the dry season the land is planted with tobacco. Based on the problems in the village, KKN PMD UNRAM students raised the theme "Healthy Village" with the topic "Building a Healthy Village with Sustainable Waste Management". The main program is making compost and making soap from organic materials. The purpose of this program is to build public awareness of the importance of health, realize quality, character, creativity and innovation and help the community's economy. One of the problems in the Jero Gunung village community, Sakra Barat District, East Lombok Regency is the lack of public awareness to live healthily, especially related to littering. This waste problem has become the biggest problem in Jero Gunung village which is difficult to eliminate. Most of this waste comes from households. In addition to the waste problem, there is also a lot of livestock waste that can be used as compost. And seen from the agricultural side, Jero Gunung village also has quite large plantation potential such as coffee, chili, tomatoes and so on. In rice fields, rice is usually planted in the rainy season while in the dry season the land is planted with tobacco. Based on the problems in the village, KKN PMD UNRAM students raised the theme "Healthy Village" with the topic "Building a Healthy Village with Sustainable Waste Management". The main program is making compost and making soap from organic materials. The purpose of this program is to build public awareness of the importance of health, realize quality, character, creativity and innovation and help the community's economy.